The Effect of Financial Performance on Stock Returns of Non- Banking Companies in Indonesia - Andre Suryaningprang; Yoyo Sudaryo; Andhika Mochamad Siddiq; Dedi Supiyadi (Greenation International Journal of Economics and Accounting, 2024)
This study objectively examines how financial performance metrics affect stock returns. ROA, ROE, CR, DER, and EVA are being examined. This study uses secondary data from external sources. This study used purposive sampling to choose a sample based on criteria. This study covers 2015–2023 Indonesia Stock Exchange (IDX) LQ 45 Index non- banking companies. Companies from the LQ 45 Index and Sri Kehati Index were carefully selected for the sample. The sample included 46 non-banking firms. As the best analysis model, panel data regression with fixed effect was used. Insignificant association exists between ROA and stock returns.